2018
DOI: 10.1371/journal.pone.0194292
|View full text |Cite
|
Sign up to set email alerts
|

A trauma network with centralized and local health care structures: Evaluating the effectiveness of the first certified Trauma Network of the German Society of Trauma Surgery

Abstract: BackgroundTrauma is a global burden of disease and one of the main causes of death worldwide. Therefore, many countries around the world have implemented a wide range of different initiatives to minimize mortality rates after trauma. One of these initiatives is the bundling of treatment expertise in trauma centers and the establishment of trauma networks.Germany has a decentralized system of trauma care medical centers. Severely injured patients ought to receive adequate treatment in both level I and level II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
(40 reference statements)
1
8
0
2
Order By: Relevance
“…Such strategies may include hotlines for rapid response in emergency cases, ambulance services for mobilizing the patients, institutionalizing protocols for trauma management guiding specific types of patients to pre-specified centers without delay, and establishing a centralized information system for coordinating the patients and health services organizations for better emergency and referral care. 83,85 Many studies in this review reported critical gaps in existing systems of reporting WPV and insufficient measures taken by the hospital authorities, which may affect the occupational engagement and personal wellbeing of the victims of WPV. Also, the physical and mental health of the victims of WPV should be taken care of alongside the administrative measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such strategies may include hotlines for rapid response in emergency cases, ambulance services for mobilizing the patients, institutionalizing protocols for trauma management guiding specific types of patients to pre-specified centers without delay, and establishing a centralized information system for coordinating the patients and health services organizations for better emergency and referral care. 83,85 Many studies in this review reported critical gaps in existing systems of reporting WPV and insufficient measures taken by the hospital authorities, which may affect the occupational engagement and personal wellbeing of the victims of WPV. Also, the physical and mental health of the victims of WPV should be taken care of alongside the administrative measures.…”
Section: Discussionmentioning
confidence: 99%
“…Such strategies may include hotlines for rapid response in emergency cases, ambulance services for mobilizing the patients, institutionalizing protocols for trauma management guiding specific types of patients to pre-specified centers without delay, and establishing a centralized information system for coordinating the patients and health services organizations for better emergency and referral care. 83,85…”
Section: Discussionmentioning
confidence: 99%
“…1 The mortality of our adolescent cohort was 0% compared to 19.4% of the total study population including adult patients. 14 Since improvements in preclinical and clinical treatment led to a decreasing rate of mortality, the question of quality of life after severe trauma gains importance. 15 Especially in cohort of younger patients, the functional impairment after injury might be of great interest, since they have an entire life to build.…”
Section: Discussionmentioning
confidence: 99%
“…The TNO was founded in 2007 and has proven to be an effective network to improve patient care of the severely injured. 7 All 25 hospitals of the TNO network participate in the trauma registry of the German Trauma Society (DGU), which was the basis for this prospective multicenter study.…”
Section: Methodsmentioning
confidence: 99%
“…The rural eastern Bavarian region is sparsely populated in comparison with metropolitan areas, entailing longer distances between clinics. 12 TNO had merely one, central maximum care provider -the Regensburg University Hospital (UKR). There were insular solutions on the telemedicine market; however, these were exclusively manufacturer-bound.…”
Section: Inter-and Intra-clinical Communication: Telecooperation Tnw mentioning
confidence: 99%